Pesan Dakwah dalam Film 99 Cahaya di Langit Eropa (Analisis Semiotika Roland Barthes) - Desi Rosmitasari (STID DI AL-HIKMAH, 2017)
Films included in the category of mass media which attracted many people because the filmmakers to convey the message of the film-making directly. Moreover, after the development of technologies in various fields including film. One of the films circulating in Indonesia is a movie 99 Light In Sky Europe Part 1, as object in this study. That's because in the film Thunder Soeharjanto contains many messages of da’wah that can be used as examples in everyday life. This research was conducted using qualitative research methods semiotic analysis of Roland Barthes theory which aims to determine the meaning of denotation and connotation of symbols contained in the film. As for how data collection is done through cutting scenes into images. Barthes analyzed using the theory to represent the symbols in the form of marks which include signs of verbal and non-verbal signs. The conclusion of this study is obtained much propaganda message which includes the fields of faith, worship and morality.